Life Satisfaction, Positive Affect, and Sleep Impairment in Masters Athletes: Modulation by Age, Sex, and Exercise Type - Wooten, Savannah V.; Mittag, Uwe; Alvero Cruz, José Ramón; Stray-Gundersen, Sten; Hoffmann, Fabian; Michély, Sarah; Möstl, Stefan; Sies, Wolfram; Mulder, Edwin; Rauschendorfer, Philipp; Chilibeck, Philip D.; Rittweger, Jörn; et al. (Frontiers in Physiology, 2021)
Introduction: The masters athlete has been proposed as a model of successful aging. Research studies investigating psychological outlook in older athletes have primarily addressed negative affects including depression, anxiety, and stress. The impact of lifelong exercise on positive affect and life satisfaction as well as sleep impairment that could impact on these psychological state is largely unknown. Methods: A series of questionnaires (general life satisfaction, positive affect, and sleep-related impairment) were administered to 240 masters athletes participating in the World Masters Athletics Championships. Total raw scores were converted into T Scores for comparison with the general population.. Meaningful difference was defined by the PROMIS® as one-half standard deviation from the centering sample. Results: Meaningful differences were seen for improved general life satisfaction and reduced sleep impairment for all masters athletes. Positive affect did not reach the meaningful difference threshold. No significant sex differences were found for any of the questionnaires (all p>0.05). Similarly, no significant differences were found between endurance, sprint, and strength/power sports for general life satisfaction (p=0.18), positive affect (p=0.46), and sleep impairment (p=0.77). In general, life satisfaction increased with age (r=0.15, p=0.02) and sleep impairment trended towards reduction with age (r=-0.13, p=0.05). Positive affected demonstrated no correlated with age (r=0.09, p=0.18). Conclusion: This study demonstrates that the lifestyles of masters athletes contribute to improved general life satisfaction and reduced sleep impairment but not improved positive affect. The beneficial effects were observed irrespective of age, gender, and sporting types.